Rationale and design of the Further cardiovascular OUtcomes Research with PCSK9 Inhibition in subjects with Elevated Risk trial - Sabatine, Marc S.; Giugliano, Robert P.; Keech, Anthony; Honarpour, Narimon; Wang, Huei; Liu, Thomas; Wasserman, Scott M.; Scott, Robert; Sever, Peter S.; Pedersen, Terje R. (The American heart journal, 2016)
Despite current therapies, patients with vascular disease remain at high risk for major adverse cardiovascular events. Low-density lipoprotein cholesterol is a well-established modifiable cardiovascular risk factor. Evolocumab is a fully human monoclonal antibody inhibitor of proprotein convertase subtilisin/kexin type 9 that reduces low-density lipoprotein cholesterol by approximately 60% across various populations. FOURIER is a randomized, placebo-controlled, double-blind, parallel-group, multinational trial testing the hypothesis that adding evolocumab to statin therapy will reduce the incidence of major adverse cardiovascular events in patients with clinically evident vascular disease. The study population consists of 27,564 patients who have had a myocardial infarction (MI), an ischemic stroke, or symptomatic peripheral artery disease and have a low-density lipoprotein ≥70 mg/dL or a non–high-density lipoprotein cholesterol ≥100 mg/dL on an optimized statin regimen. Patients were randomized in a 1:1 ratio to receive either evolocumab (either 140 mg subcutaneously every 2 weeks or 420 mg subcutaneously every month, according to patient preference) or matching placebo injections. The primary end point is major cardiovascular events defined as the composite of cardiovascular death, MI, stroke, hospitalization for unstable angina, or coronary revascularization. The key secondary end point is the composite of cardiovascular death, MI, or stroke. The trial is planned to continue until at least 1,630 patients experience the secondary end point, thereby providing 90% power to detect a relative reduction of ≥15% in this end point. FOURIER will determine whether the addition of evolocumab to statin therapy reduces cardiovascular morbidity and mortality in patients with vascular disease.